2019
DOI: 10.1002/advs.201900610
|View full text |Cite
|
Sign up to set email alerts
|

A Proresolving Peptide Nanotherapy for Site‐Specific Treatment of Inflammatory Bowel Disease by Regulating Proinflammatory Microenvironment and Gut Microbiota

Abstract: The incidence and prevalence of inflammatory bowel disease (IBD) increases steadily worldwide. There is an urgent need for effective and safe IBD therapies. Accelerated resolution of inflammation is a new strategy for the management of inflammatory diseases. For effective and safe IBD treatment, herein a smart nanotherapy (i.e. oxidation‐responsive nanoparticles containing a proresolving annexin A1‐mimetic peptide Ac2‐26, defined as AON) is developed, which can release packaged Ac2‐26, in response to highly ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 131 publications
(102 citation statements)
references
References 72 publications
3
97
0
Order By: Relevance
“…For instance, by taking advantages of the elevated ROS level in ulcerative colon 8 , the ROS-responsive nanoparticles (NPs) based on β-cyclodextrin derivatives firstly developed by Zhang and Li et al exhibited an excellent safety profile, improved drug accumulation in the inflammatory colon, and enhanced the therapeutic efficacy against UC 9 . With the same ROS-responsive nanomedicine platform, pro-resolving peptide Ac2-26 was released in the high ROS environment specifically in the UC colon, driving inflammatory resolution effectively 10 . In spite of these significant progresses, many challenges still exist with these novel nanomedicines, such as low accumulation in the colon tissues, fast clearance, and little distinction in actions on different cell types.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, by taking advantages of the elevated ROS level in ulcerative colon 8 , the ROS-responsive nanoparticles (NPs) based on β-cyclodextrin derivatives firstly developed by Zhang and Li et al exhibited an excellent safety profile, improved drug accumulation in the inflammatory colon, and enhanced the therapeutic efficacy against UC 9 . With the same ROS-responsive nanomedicine platform, pro-resolving peptide Ac2-26 was released in the high ROS environment specifically in the UC colon, driving inflammatory resolution effectively 10 . In spite of these significant progresses, many challenges still exist with these novel nanomedicines, such as low accumulation in the colon tissues, fast clearance, and little distinction in actions on different cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Dextran sulfate sodium salt (DSS) disrupts the mucosal barrier of the colon, causing intestinal inflammation, weight loss, and other clinical symptoms, thus becoming a common agent for clinically induced colitis 40 . C57/BL6 mice in the experimental group were orally treated with DSS ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, our studies showed that OxbCD nanoparticles are able to package a proresolving annexin A1-mimetic peptide Ac2-26, offering a ROS-responsive peptide nanotherapy (defined as AON) ( Fig. 6 A-E) [ 321 ]. AON effectively protected Ac2-26 from degradation in the gastrointestinal environment ( Fig.…”
Section: Treatment Of Inflammatory Diseases By Bioresponsive Drug Delmentioning
confidence: 99%